The Influence Of Brand Image, Product Quality, And Price On Brand Switching Of Wardah Makeup In Bengkulu City - Peli Rahmita Sari; Ida Ayu Made E.G; Zoniarti Zoniarti (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
When buying an item, a consumer often assesses whether the item is suitable for them or not, whether it is suitable for them or not, therefore consumers prioritize choosing by looking at the brand image, product quality and price to fulfill their desires or needs in purchasing goods. The aim of this research is to determine the influence of brand image, product quality and price on brand switching of Wardah makeup products in Bengkulu City. The type of research used is quantitative. The data analysis methods used are multiple linear regression, determination tests, and hypothesis tests. The results of multiple linear regression have the equation Y = 54, 534 - 0.395(X1) - 0.007(X2) - 0.404(X3) + 3.602 because the direction of the regression is positive, it can be interpreted that if brand image, product quality and price increase, then interest in buying Wardah's makeup product in Bengkulu City will also increase. Brand image does not have a significant effect on interest in buying Wardah makeup products in Bengkulu City, this is proven by the value of t count is smaller than t table (-5, 324 < 1.659) and a significant value of 0.000 < 0.05 meaning that H0 is accepted and Ha is rejected. Product quality has a significant effect on interest in buying Wardah makeup products in Bengkulu City, this is proven by the value of t count is greater than t table (-0.065 < 1.659) with a significant value of 0.984 > 0.05 meaning H0 is rejected and Ha is accepted. Price has a significant effect on interest in buying Wardah makeup products in Bengkulu City, this is proven by the value of t count is greater than t table (-6,200 < 1.659) with a significant value of 0.000 - 0.05 meaning H0 is rejected and Ha is accepted. Brand image (X1), product quality (X2), and price (X3) together have a significant effect on brand switching (Y) of Wardah makeup products in Bengkulu City.